Superlubricity of dry nanocontacts - Gnecco, Enrico; Maier, Sabine; Meyer, Ernst (Journal of Physics: Condensed Matter, 2008)
We discuss how various forms of dry superlubricity, recently observed on the nanoscale, have been interpreted by simple phenomenological models. In particular, we review the cases of static and dynamic single-contact lubricity, thermolubricity, and structural lubricity. All these phenomena have been studied by friction force microscopy and explained using the classical Prandtl-Tomlinson model and its extensions, including thermal activation, temporal and spatial variations of the surface energy corrugation, and multiple-contact effects. © 2008 IOP Publishing Ltd.
Created from Fastlane, Scopus look-up